Identifikasi Degradasi Tutupan Lahan dan Kerapatan Vegetasi Menggunakan Algoritma Normalized Difference Vegetation Index (NDVI) Berbasis Sistem Informasi Geografis di Kabupaten Sidoarjo - Sari Cahya Putri; Sukma Perdana Prasetya (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Land vegetation cover change is an important indicator for assessing the environmental condition of a region and can be influenced by various factors, including population growth. Sidoarjo Regency, as one of the buffer areas of Surabaya City, has experienced rapid regional development, which has the potential to affect vegetation conditions. This study aims to analyze changes in vegetation land cover in Sidoarjo Regency from 2020 to 2025 using the Normalized Difference Vegetation Index (NDVI) method based on Geographic Information Systems (GIS) and to examine its relationship with population growth. The data used consisted of Landsat satellite imagery from 2020–2025 and population data of Sidoarjo Regency obtained from the Central Statistics Agency (BPS). The analysis was conducted through satellite image processing to obtain NDVI values, spatial mapping of vegetation land cover, analysis of NDVI value changes, and Pearson correlation analysis between NDVI values and population size. The results showed that the average NDVI values of Sidoarjo Regency during the study period ranged from 0.38536 to 0.41624, indicating the dominance of moderate vegetation cover. The highest NDVI value occurred in 2022 at 0.41624, while the lowest value was recorded in 2023 at 0.38536. The correlation analysis produced a correlation coefficient of -0.294, indicating a weak negative relationship between population growth and changes in vegetation land cover. Thus, population growth has not been the dominant factor influencing vegetation land cover changes in Sidoarjo Regency during the 2020–2025 period. Other factors, such as land use, agricultural activities, environmental conditions, and spatial planning policies, are also suspected to contribute to vegetation dynamics in the study area.